Inequality in incomes and access to education : a cross-country analysis - Checchi, Daniele (WIDER working papers, ISSN 0782-8233, 1999)
Abstract (s. vi).
Keywords: tulonjako : perhe; tulonjako : kansainvälinen vertailu; koulutus : kansainvälinen vertailu; yhdenvertaisuus : koulutus